THE NEW RULES OF ENTREPRENEURSHIP: HOW TO THRIVE IN AN AI-DRIVEN ECONOMY - Aspizain Caniago; Edison Parlindungan; Istna Fibriyadi; Inna Hanarti; Wuly Sudarmi (MANAGER: Journal of Management and Administration Science, 2025)
The rapid advancement of Artificial Intelligence (AI) is redefining the foundations of entrepreneurship, reshaping business models, workforce structures, and competitive dynamics in the global economy. This study aims to examine the emerging rules of entrepreneurship in an AI-driven economy and to identify strategic capabilities required for sustainable entrepreneurial success. The research employs a qualitative-descriptive approach based on an integrative literature review of recent scholarly works on AI-driven entrepreneurship, business model innovation, process automation, digital economy transformation, and workforce agility. Key sources include contemporary analyses of AI-enabled business model transformation, AI-driven process innovation in startups, and the role of workforce adaptability in sustaining entrepreneurial growth. The findings reveal that thriving in an AI-driven economy requires entrepreneurs to develop five core competencies: AI literacy and data-driven decision-making; business model innovation and digital scalability; process automation and intelligent optimization; workforce agility and continuous learning; and ethical, sustainable AI governance. AI is not merely an operational tool but a strategic infrastructure that lowers entry barriers, accelerates innovation cycles, enhances personalization, and enables predictive strategic management. However, successful AI adoption depends on ecosystem readiness, educational reform, and responsible governance frameworks. The study concludes that the new rules of entrepreneurship are defined by adaptability, technological integration, and sustainability. Entrepreneurs who strategically combine AI capabilities with dynamic organizational learning and responsible innovation are more likely to achieve resilience, competitiveness, and long-term value creation in the Fourth Industrial Revolution.